2015
DOI: 10.1111/liv.12846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of portal hypertension by real‐time shear wave elastography in cirrhotic patients

Abstract: In cirrhotic patients, LSM by SWE is highly correlated with HVPG value regardless of ascites. SWE is a new reliable non-invasive diagnostic tool to predict CSPH and SPH, even in cirrhotic patients with ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 30 publications
7
44
2
1
Order By: Relevance
“…Recent studies introduced Shear-wave elastography of the liver (L-SWE) as a promising tool to diagnose portal hypertension. [10][11][12] These studies find good diagnostic accuracy of L-SWE with specificity and sensitivity ranging between 80% and 90%, which was partly better compared head-to-head with TE. Using two different cut-offs to rule-in and rule-out CSPH, sensitivity and specificity could be increased up to more than 90%.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recent studies introduced Shear-wave elastography of the liver (L-SWE) as a promising tool to diagnose portal hypertension. [10][11][12] These studies find good diagnostic accuracy of L-SWE with specificity and sensitivity ranging between 80% and 90%, which was partly better compared head-to-head with TE. Using two different cut-offs to rule-in and rule-out CSPH, sensitivity and specificity could be increased up to more than 90%.…”
Section: Introductionmentioning
confidence: 75%
“…Firstly, TE is useless in patients with ascites; secondly, TE shows high failure rates in obese patients especially in patients with a BMI >30 kg/m 2 ; thirdly, TE offers only a regional elasticity measurement, but no anatomical image; and fourthly, the small sample size is by definition not representative for the whole liver . Therefore, SWE has already been introduced as a promising and equally accurate tool to diagnose portal hypertension and the stage of liver fibrosis and cirrhosis in chronic liver disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver-stiffness measurements obtained during different breathing phases were described in previous papers where patients were asked to hold their breath [15][16][17]. The authors of those studies considered the same two breathing phases and found that liver stiffness at end-expiration was significantly higher than that at end-inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study on pigs [14] demonstrated that liver stiffness measures with transient elastography (Fibroscan, Echosens) was directly affected by central venous pressure, which is increased during a Valsalva maneuver. In addition, a recent study using SWE technology on 115 cirrhotic patients showed that liver-stiffness measurements were strongly correlated with the hepatic venous pressure gradient [15]. Hence, asking patients to hold their breath could lead to overestimation of liver stiffness.…”
Section: Discussionmentioning
confidence: 99%